2022
DOI: 10.1101/2022.08.05.502982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phanta: Phage-inclusive profiling of human gut metagenomes

Abstract: The human gut microbiome is a diverse ecosystem that encompasses multiple domains of life and plays a vital role in human health. Due to technical limitations, most microbiome studies have focused on gut prokaryotes, overlooking bacteriophages and other gut viruses. The most common method to profile viruses is to assemble shotgun metagenomic reads - often from virus-enriched samples - and identify viral genomes de novo. While valuable, this resource-intensive and reference-independent method has limited sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…The extreme abundance of the phage reads in the metagenomic datasets are, to our knowledge, an unparalleled observation. While viruses typically comprise a small part (~5%) of total metagenome datasets 54 , previous studies showed that bacteriophages sometimes account for a considerable fraction of DNA sequence reads, even though their genomes are relatively small compared to those of cellular organisms. For example, crAssphage accounted for up to 22% of sequencing reads in total community shotgun metagenomes from human stool samples 55 , and in another study, viruses accounted for 4-17% of the total community metagenome reads, also from human stool 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The extreme abundance of the phage reads in the metagenomic datasets are, to our knowledge, an unparalleled observation. While viruses typically comprise a small part (~5%) of total metagenome datasets 54 , previous studies showed that bacteriophages sometimes account for a considerable fraction of DNA sequence reads, even though their genomes are relatively small compared to those of cellular organisms. For example, crAssphage accounted for up to 22% of sequencing reads in total community shotgun metagenomes from human stool samples 55 , and in another study, viruses accounted for 4-17% of the total community metagenome reads, also from human stool 56 .…”
Section: Discussionmentioning
confidence: 99%